2021
DOI: 10.3906/sag-2010-18
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the expression levels of CPEB4, APC, TRIP13, EIF2S3, EIF4A1, IFNg, PIK3CA and CTNNB1 genes in different stage colorectal tumors

Abstract: The aim of the study is to assess expression levels of CPEB4, APC, TRIP13, EIF2S3, EIF4A1, IFNg, PIK3CA and CTNNB1 genes in tumors and peripheral bloods of colorectal cancer patients in stages I-IV. Materials and methods: The mRNA levels of the genes were determined in tumor tissues and peripheral blood samples of 45 colorectal cancer patients and colon tissues and peripheral blood samples of 5 healthy individuals. Real-time polymerase chain reaction method was used for the analysis.Results: The mRNA level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
0
12
0
1
Order By: Relevance
“…The real-time RT-PCR technique was recently applied to measure expression levels of CPEB4 , APC , TRIP13 , EIF2S3 , EIF4A1 , IFNg , PIK3CA, and CTNNB1 genes in tumors and peripheral blood samples of colorectal cancer patients in stages I–IV of the disease [ 25 ]. Total RNA was extracted from tissues or peripheral blood samples, followed by reverse transcription to produce cDNA.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The real-time RT-PCR technique was recently applied to measure expression levels of CPEB4 , APC , TRIP13 , EIF2S3 , EIF4A1 , IFNg , PIK3CA, and CTNNB1 genes in tumors and peripheral blood samples of colorectal cancer patients in stages I–IV of the disease [ 25 ]. Total RNA was extracted from tissues or peripheral blood samples, followed by reverse transcription to produce cDNA.…”
Section: Applicationsmentioning
confidence: 99%
“…Using specific primers for each gene, real-time PCR was then performed to analyze the mRNA level of each gene in colorectal cancer tissue specimens, colorectal cancer blood samples, normal colon tissues, and normal blood samples. The study concluded that TRIP13 and CPEB4 mRNA up-regulation in the peripheral blood of patients with colorectal cancer might be a potential target for an early-stage test of colorectal cancer [ 25 ]. Similarly, the real-time RT-PCR method was employed to determine and evaluate the microRNAs (miR-150, miR-146a, hsa-let-7e) expression profile within peripheral blood mononuclear cells (PBMCs) infected with the dengue virus.…”
Section: Applicationsmentioning
confidence: 99%
“… Zhu et al (2019 ) found that TRIP13 was the most prominent differentially expressed AAA ATPase gene and a promising candidate oncogene in liver cancer. In addition, the TRIP13 mRNA level was upregulated in peripheral blood in colon cancer tissues, thus making it a potential target for early-stage diagnosis ( Soylemez et al, 2021 ). Nevertheless, no literature showed its association with stomach cancer, and further research is needed.…”
Section: Resultsmentioning
confidence: 99%
“…Понижение экспрессии генов MMD, TLR1, возможно, соотносится со снижением иммунной функции у пациентов с КРР [18,19]. Ген CPEB4, являющийся регулятором трансляции широкого спектра действия, может быть поразному экспрессирован на разных стадиях КРР [20], для построения модели 1 на нашей выборке имела значение его пониженная экспрессия.…”
Section: Discussionunclassified